A Typology of Rebel Political Institutional Arrangements. (January 2021) - Mampilly, Zachariah; Stewart, Megan A.
What are the different political institutions rebels create to engage captive civilian populations, and how do they arrive at distinct political arrangements? Rebel-controlled territories host a diversity of political institutions ranging from structures designed to promote democratic decision-making to martial law. Although previous research has focused on rebel social service provision and other aspects of rebel governance, few have investigated variation in the institutional arrangements rebels adopt. In this article, we identify a set of four dimensions along which rebel political institutions vary leading to six ideal–typical forms of political arrangements. We argue that an iterative and dynamic stepwise process, determined by rebel group strategies and local conditions, produces one of these political institutional outcomes. Importantly, the type of rebel political institutions within one location can change throughout the war, and variation sometimes emerges across territories the same rebel group controls. We demonstrate the plausibility of our arguments through a series of illustrative case studies that correspond to the formation processes of our six ideal–typical political arrangements. We conclude with recommendations for future research.